Spectrum-aware mobile computing : convergence of cloud computing and cognitive networking /: convergence of cloud computing and cognitive networking. ([2019]) - Mahmoodi, Seyed Eman; Subbalakshmi, Koduvayur; Uma, R. N
No abstract available